Alkyds with artistic applications based on drying oils, multifunctional polyalcohols and different polybasic acids - Bellatin Arciniega, L.; Meza Yapu, R.; Obregón-Valencia, D.; Hadzich, A.; Costa, M.A.; Ispas, A.; Bund, A.; Flores, S. (John Wiley and Sons, 2023)
Today's requirements in the art field have challenged researchers to create artistic paintings with attractive appearance and long-term color stability. Alkyd-based art mediums have become an important group in the art field, because of their similar characteristics to traditional oils and exceptional drying properties. In this work, high solid alkyd-based art mediums have been synthesized by the monoglyceride and acidolysis processes. Multifunctional polyols and high unsaturated fatty acid sources were compared and used for alkyd synthesis. The use of a non-traditional oil of Peruvian origin is proposed. Resins have been characterized according to their physicochemical (acid number, viscosity, color and density) and drying properties. Drying tendencies were verified with the use of quartz crystal microbalance. Also, the behavior of the art mediums mixed with commercial oil paintings and a dry pigment, have also been evaluated. Results indicate that resins containing the polyol with the highest functionality are more viscous and have fewer tendencies to yellowing, while non-traditional Peruvian oil is the best option for creating light-colored art mediums. Alkyd mediums prepared by the monoglyceride method gave to oil paintings better characteristics and drying behavior on canvas.
Keywords: Alkyd; Monoglyceride; Materials science; Polyol; Chemical engineering; Viscosity; Polymer science; Organic chemistry; Chemistry; Nanotechnology; Coating; Composite material; Fatty acid; Polyurethane; https://purl.org/pe-repo/ocde/ford#1.04.03